Structural, dielectric and electrical properties of Gd-substituted lithium nano-ferrites prepared by the WOWS sol-gel method - Hanif, M. (Institute of Physics Publishing, 2020)
To synthesize lithium ferrite with various Gd concentrations (Li0.5Fe2.5-xGdxO4), x = 0.00, 0.025, 0.05, 0.075, 0.1, solutes were dissolved in glycol, i.e. by using the without water and surfactant (WOWS) sol-gel method. X-ray diffraction (XRD) analysis confirmed that the material possessed an inverse spinel cubic structure and is single phase. Pellets of all samples were sintered at 700 °C and XRD confirmed that samples were crystalline, phase pure and had an inverse spinel cubic lattice. Scanning electron microscopy indicated that the grains were agglomerated and had a predominantly spherical shape. It is concluded that Gd acts as a grain refiner in lithium ferrite up to a Gd concentration of 0.05. AC conductivity and dielectric constant increased by increasing Gd concentration. The Maxwell-Wagner model and Johnsher's power law were used to explain the dielectric properties. DC conductivity was measured from 100 to 600 °C. DC conductivity was explained by the hopping mechanism. It is concluded that DC resistivity and dielectric constant values are related reciprocally in the prepared sample. AC electrical properties were also measured at a constant frequency of 1 MHz in the temperature range from 400 to 600 °C. Gd-substituted lithium ferrite showed high AC conductivity, high DC resistivity and constant dielectric values, but low dielectric loss values as compared to pure lithium ferrite. © 2020 IOP Publishing Ltd.